Globalization Versus Adaptation Strategy in International Marketing: A Study of Exporting Companies in The Peoples Republic of China - Gabriel O. Ogunmokun,; Ling-Yee Li, (Asian Academy of Management Journal, 1999)
According to Shaw and Onkvist (1987) and Akhter (1995) the issue of global standardization or adaptation in international marketing is not just another theoretical concept in search of practical application. It is a significant issue which warrants attention and evalution. For example, if global standardization is better than adaptation, it should have far-reaching implications for management because of its effect on business firms, advertising agencies, consumers and marketing aducation etc. However, according to Hoang (1997), although much has been said and written in the area of globalization/customization, and standardization/adaptation, emprical research examining the desirability of such concepts has been relatively limited. This paper presents the findings of a study in China that examined whether there are significant differences in the adaptation strategy used by firms when they were successful in their product export ventures versus when they were unsuccessful